Assessing the factors influencing employee attrition at selected Business Process Outsourcing Company: A retention-reinforcement approach - Boticario, Khristine Mae G., Chua, Mary Grace B., De Jesus, Katherine R., De Leon, Janna Rizzle S., Esteban, Danica Ann F., Estrellado, Dellesy Marie D., Tapar, Mycel Jane T. 4 0 16; 5
Abstract The Business Process Outsourcing (BPO) industry is renowned for its demanding and high- stress work environment, making it an attractive but challenging sector for employees. However, many employees leave their jobs quickly, which makes it hard for companies to find qualified workers. Hence, Business Process Outsourcing companies are struggling with the significant challenge of retaining their workforce due to high turnover. This study primarily aims to investigate the various influencing factors of the attrition of employees from selected BPO Company in Mall of Asia (MOA), Pasay City. This study addresses the current attrition level of the company through workplace culture, compensation and benefits, career advancement, and inefficient management. The researchers employed descriptive research to facilitate the identification and measurement of the associations between multiple variables and to describe the situation thoroughly. Furthermore, the researchers utilized a purposive sampling technique based on the employees' influencing factors, wherein the respondents for this study are the current employees of the company. The researchers also used a survey-based approach to gather primary data from participants. The assessment tool prepared for this study was administered through an online questionnaire that was designed in four distinct sections. Encompassing a total of 24 questions in the form of a Likert scale and multiple-choice to assess participants' personal information, experiences, and responses. Overall, the total number of responses needed to complete this study is 237 for selected BPO company employees. The data gathered from the respondents of the study will be interpreted using the following statistical methods: Slovin's formula, Frequency, and Percentage Distribution, Weighted Mean, Standard Deviation, Analysis of Covariance (ANCOVA) and Spearman Rho Correlation. In conclusion, the goal of the study is to assist the company in navigating the necessary steps to enhance the organization's operations, particularly in strengthening employment satisfaction, amplifying equilibrium between work and personal life, and ultimately fostering a more sustainable and positive occupational environment for its employees to remain competitive in the Business Process Outsourcing (BPO) industry.
Business Research: (BSBA major in Human Resource Management) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2